PERANCANGAN IKLAN LAYANAN MASYARAKAT MENCEGAH KEBAKARAN HUTAN DI PALEMBANG SUMATERA SELATAN - Muhammad Ajie Danu Wijaya; Husni Mubarat; Aji Windu Viatra (Besaung : Jurnal Seni Desain dan Budaya, 2017)
Public Service Ads (PSAs) are ads that present social messages that are ready to raise public awareness of the goods they should have, whose conditions can be aligned and public life. This Community Service advertisement is very sociable that emphasizes the interest of the community who likes to instil awareness of the community about important social issues. The choice of design themes of Public Service Ads serves to inform the government and the public. Expected by the design of this ad more than what we want and prepare for fire hazard. Key words: Public Service Ads, Forest Fires